A study on Women reservation in MGNREGA (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The main objective of this research work examines the efficiency of public works implementation when a state and center government has one third seat reserved for female candidates versus those that are not. I use many detailed and information on employment and public works expenditure under the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) from 2010 to 2013 for 6222 Panchayats in 22 districts in the state of Haryana and combine this with information on local level electoral information. Exploiting the randomized assignment of female candidate reservations, we find that demand for work and women's labour force participation Signiant increase in Panchayats with female leader. However, we find no significant effects on the type of work.